Identification of Myoferlin, a Potential Serodiagnostic Antigen of Clonorchiasis, via Immunoproteomic Analysis of Sera From Different Infection Periods and Excretory-Secretory Products of Clonorchis sinensis - Ma, Xiao-Xiao; Qiu, Yang-Yuan; Chang, Zhi-Guang; Gao, Jun-Feng; Jiang, Rui-Ruo; Li, Chun-Lin; Wang, Chun-Ren; Chang, Qiao-Cheng (Frontiers in Cellular and Infection Microbiology, 2021)
Clonorchiasis, which is caused by Clonorchis sinensis, is an important foodborne disease worldwide. The excretory-secretory products (ESPs) of C. sinensis play important roles in host-parasite interactions by acting as causative agents. In the present study, the ESPs and sera positive for C. sinensis were collected to identify proteins specific to the sera of C. sinensis (i.e., proteins that do not cross-react with Fasciola hepatica and Schistosoma japonicum) at different infection periods. Briefly, white Japanese rabbits were artificially infected with C. sinensis, and their sera were collected at 7 days post-infection (dpi), 14 dpi, 35 dpi, and 77 dpi. To identify the specific proteins in C. sinensis, a co-immunoprecipitation (Co-IP) assay was conducted using shotgun liquid chromatography tandem-mass spectrometry (LC-MS/MS) to pull down the sera roots of C. sinensis, F. hepatica, and S. japonicum. For the annotated proteins, 32, 18, 39, and 35 proteins specific to C. sinensis were pulled down by the infected sera at 7, 14, 35, and 77 dpi, respectively. Three proteins, Dynein light chain-1, Dynein light chain-2 and Myoferlin were detected in all infection periods. Of these proteins, myoferlin is known to be overexpressed in several human cancers and could be a promising biomarker and therapeutic target for cancer cases. Accordingly, this protein was selected for further studies. To achieve a better expression, myoferlin was truncated into two parts, Myof1 and Myof2 (1,500 bp and 810 bp), based on the antigenic epitopes provided by bioinformatics. The estimated molecular weight of the recombinant proteins was 57.3 ku (Myof1) and 31.3 ku (Myof2). Further, both Myof1 and Myof2 could be probed by the sera from rabbits infected with C. sinensis. No cross-reaction occurred with the positive sera of S. japonica, F. hepatica, and negative controls. Such findings indicate that myoferlin may be an important diagnostic antigen present in the ESPs. Overall, the present study provides new insights into proteomic changes between ESPs and hosts in different infection periods by LC-MS/MS. Moreover, myoferlin, as a biomarker, may be used to develop an objective method for future diagnosis of clonorchiasis.